2016
DOI: 10.1002/psc.2958
|View full text |Cite
|
Sign up to set email alerts
|

Biological and structural effects of the conjugation of an antimicrobial decapeptide with saturated, unsaturated, methoxylated and branched fatty acids

Abstract: The increasing bacterial resistance against conventional antibiotics has led to the search for new antimicrobial drugs with different modes of action. Cationic antimicrobial peptides (AMPs) and lipopeptides are promising candidates to treat infections because they act on bacterial membranes causing rapid destruction of sensitive bacteria. In this study, a decapeptide named A2 (IKQVKKLFKK) was conjugated at the N-terminus with saturated, unsaturated, methoxylated and methyl -branched fatty acids of different ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…The introduction of fatty acids in AMPs can improve the ability to form secondary structures or oligomerization when interacting with bacterial membrane, thereby improving the antimicrobial effect. Herein, a series of lipopeptides (Table ) were synthesized by modifying P1 with fatty acids, which had the best activity among the four skeletons (Table ). Figure c is the line model of GLP6, and the MS spectra of AMPs are shown in Figure d and Figure S1, which indicated the AMPs were successfully synthesized.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The introduction of fatty acids in AMPs can improve the ability to form secondary structures or oligomerization when interacting with bacterial membrane, thereby improving the antimicrobial effect. Herein, a series of lipopeptides (Table ) were synthesized by modifying P1 with fatty acids, which had the best activity among the four skeletons (Table ). Figure c is the line model of GLP6, and the MS spectra of AMPs are shown in Figure d and Figure S1, which indicated the AMPs were successfully synthesized.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The pure cis enantiomer 18 did not differ in activity from the mixture 15 . These observed antifungal activities are also significantly higher than those recently reported for the cationic peptidomimetics prepared by Larsen et al and the fatty acid AMP conjugates reported by Húmpola and coworkers …”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated by Húmpola et al, lipopeptides with longer chains of C17 and C20 were not active against bacteria and Candida species, probably due to their strong ability to self-assemble, whereas the best activity was observed for lipopeptides with fatty acids of C8 and C14 with an MIC of between 0.7 and 5.8 μM [ 89 ].…”
Section: Amp Lipidationmentioning
confidence: 99%